ENHANCING DIGITAL MARKETING SKILL FOR EMPLOYEES OF BERYL`S CHOCOLATE FACTORY, MALAYSIA - Anggia Sari Lubis; Muhammad Rahmat; Sri Rahayu; Clarissa Tarigan (RADJA PUBLIKA, 2025)
Employee digital marketing skills are highly sought after in today's digital age. As a result, organizations are investing in their employee's digital marketing skills to remain competitive. Enhancing digital marketing skills in employees can be achieved through various training methods and tools. Beryl’s Chocolate and Confectionery Sdn. Bhd. was created with one single aim – excellence. Since the company was established in 1995, the focus has been to produce the very best chocolates for both the local and global markets. Digital marketing is important for Beryl's Chocolate because it helps the company reach more potential customers and compete with other brands.This community empowerment will increase the uses of Beryl's digital marketing tools, including social media, e-commerce, and online reviews.